Evaluation of Voice Codecs of VoIP Applications for MANET (International Journal of Current Engineering and Technology, 2014)
Over Internet (VOIP) is an emerging popular Internet application that provides good services through Mobile Adhoc Network(MANET).MANET provides a suitable platform for the deployment of voice and multimedia session over IP network in many application scenarios that range from safety to comfort related services. But this network also faces many challenges on QoS issues due to packet loss because of transmission errors, short battery life and dynamic changing topologies. WiMAX is a wireless 4G technology, currently using by various industries &institutions which provides many advantages due to its high speed and large coverage area. Combining these technology together, in this paper we estimated the performance of various VOIP codecs with WiMAX in different scenarios (sparse and dense) over MANET. Voice codecs are evaluated with some QoS metrics such as average MOS, average jitter, average throughput, average delay and signal received with error. The performance & quality of VOIP applications using H.323 signaling protocol in Qualnet 6.1 simulator are studied in order to determine their effect on QoS and find out most efficient network specific voice codec .
Keywords: VoIP, QoS, Codecs, WiMAX, MANET